Does risk sorting explain bubbles? - Hubert J. Kiss; László Á. Kóczy; Ágnes Pintér; Balázs R. Sziklai (Hungarian Academy of Sciences, Institute of Economics, 2019)
A recent stream of experimental economics literature studies the factors that contribute to the emergence of financial bubbles. We consider a setting where participants sorted according to their degree of risk aversion trade in experimental asset markets. We show that risk sorting is able to explain bubbles partially: Markets with the most risk-tolerant traders exhibit larger bubbles than markets with the most risk averse traders. In our study risk aversion does not correlate with gender or cognitive abilities, so it is an additional factor that helps understand bubbles.
Keywords: C91; G12; 330; externalities; experiment; risk sorting; asset bubble